Ethical challenges when caring for dying children. (March 2015) - Furingsten, Lovisa; Sjögren, Reet; Forsner, Maria
Background: Caring for dying children presents special challenges, according to the children themselves, their relatives and healthcare professionals. Objective: The aim of this study was to describe caring as represented in healthcare workers' experiences of caring for dying children. Method: A phenomenological approach was chosen, in-depth interviews were carried out and data were analysed in four steps focusing on (a) open reading, (b) meaning units, (c) constituents and (d) essence. Ethical considerations: Four nurses in a general acute paediatric care setting in Sweden participated after providing written informed consent. Voluntary participation and confidentiality were ensured, and the study was ethically approved. Findings: The essence of caring for dying children was likened to a musically attuned composition, comprising five constituents: presence, self-knowledge, injustice in dying, own suffering and in need of others. Presence was found to be a prerequisite for caring when a child is dying. Self-knowledge and support from others can be of help when struggling with emotional pain and injustice. Discussion: Caring for dying children has been found to be a delicate task for healthcare workers all over the world, and the ethical dimension is emphasized in international research. In this study, emotional pain and suffering accompanied caring, but an atmosphere in which it is possible to give and get support from colleagues and to have time to grieve and time to focus on the patient's needs may ease the burden, as can having time to process thoughts about life and death, and a possibility to grow in self-knowledge. Conclusion: Caring in ethically demanding situations may be facilitated through presence, atmosphere, self-knowledge and time. The challenge does not demand highly technological solutions; these assets are readily available, no matter where on earth. However, there is a need to further investigate these prerequisites for caring, particularly when a child is dying.